Does self-reported well-being of patients with Parkinson's disease influence caregiver strain and quality of life? - Peters, M; Fitzpatrick, R; Doll, H; Playford, D; Jenkinson, C (2011)
Background: The impact of Parkinson's disease (PD) on the quality of life of both patients and their carers has not been well documented. Objective: This study describes the health status of both PD patients and caregivers as measured on a generic measure of health status (SF-12), and then explores to what extent patient self-reported health, as measured on the disease-specific Parkinson's Disease Questionnaire (PDQ-39), is associated with carer strain and self-reported quality of life. Methods: A postal survey was carried out of both patients and caregivers through local branches of Parkinson's UK. Questionnaire packs were sent to those on the database with a diagnosis of PD. The patient was asked to give the carer questionnaire to their main caregiver, if they had one. Results: Results from the SF-12 suggests that PD has substantial adverse effects on both the physical and mental well-being of patients when compared with population norms. While carer physical health was not found to be substantially different from that of the general population, emotional health was lower than that of the general population. Furthermore, results suggest that the self-reported health status of PD patients is associated with higher levels of caregiver strain and poorer emotional health. Conclusion: PD impacts on both the well being of both patients and caregivers; the data provide evidence that the health status of the patient, in particular their physical health, has a significant impact on the well-being of their caregiver. © 2011 Elsevier Ltd.